Effect of preharvest conditions on cut-flower quality - Verdonk, Julian C.; van Ieperen, Wim; Carvalho, Dália R. A.; van Geest, Geert; Schouten, Rob E. (Frontiers in Plant Science, 2023)
The cut flower industry has a global reach as flowers are often produced in countries around the equator and transported by plane or ship (reefer) mostly to the global north. Vase-life issues are often regarded as linked to only postharvest conditions while cultivation factors are just as important. Here, we review the main causes for quality reduction in cut flowers with the emphasis on the importance of preharvest conditions. Cut flower quality is characterised by a wide range of features, such as flower number, size, shape, colour (patterns), fragrance, uniformity of blooming, leaf and stem colour, plant shape and developmental stage, and absence of pests and diseases. Postharvest performance involves improving and preserving most of these characteristics for as long as possible. The main causes for cut flower quality loss are reduced water balance or carbohydrate availability, senescence and pest and diseases. Although there is a clear role for genotype, cultivation conditions are just as important to improve vase life. The role of growth conditions has been shown to be essential; irrigation, air humidity, and light quantity and quality can be used to increase quality. For example, xylem architecture is affected by the irrigation scheme, and the relative humidity in the greenhouse affects stomatal function. Both features determine the water balance of the flowering stem. Light quality and period drives photosynthesis, which is directly responsible for accumulation of carbohydrates. The carbohydrate status is important for respiration, and many senescence related processes. High carbohydrates can lead to sugar loss into the vase water, leading to bacterial growth and potential xylem blockage. Finally, inferior hygiene during cultivation and temperature and humidity control during postharvest can lead to pathogen contamination. At the end of the review, we will discuss the future outlook focussing on new phenotyping tools necessary to quantify the complex interactions between cultivation factors and postharvest performance of cut flowers.